Oral diseases and systemic conditions: correlation analyses from the Colombian national health records between 2016 and 2023 - Usuga-Vacca, Margarita; Díaz-Báez, David; Beltrán, Edgar O.; Cortes, Andrea; Vargas-Sanchez, Paula Katherine; Avila, Viviana (Frontiers in Oral Health, 2024)
IntroductionPrevalence of oral, metabolic, circulatory, and nutritional diseases has tended to increase globally. As these diseases have common contributing factors, such as unhealthy diets, evaluating their epidemiological trends and the relation between them is relevant. In Colombia, the Ministry of Health records the frequency of consultation for these diseases through the Integrated Social Protection Information System. It facilitates the evaluation of their epidemiological behavior at the population level.AimTo analyze and correlate the burden of oral diseases (caries and periodontitis) with respect to nutritional, circulatory and metabolic pathologies, as well as their relationships with socioeconomic indices in Colombian regions from 2016 to 2023.MethodsThis study analyzes retrospective data collected between 2016 and 2023 by the National Health Registry in Colombia (SISPRO) according to the ICD-10. Sociodemographic data and the number of disease consultations were extracted. The number of consultations for oral diseases was correlated with systemic pathologies, socioeconomic indices through the Spearman test. Associations were explored via multiple linear regressions. A Principal Component Analyses (PCA) was conducted to identify patterns between socioeconomic, oral and systemic disease variables, as well as to reduce the complexity of the analysis by creating clusters that capture the greatest possible variability in the data.ResultsThe average number of consultations per biennium was 24.550.435 being the highest number for 2018–2019. The highest percentage of consultations was related to extensive caries, followed by chronic gingivitis. Moreover, consultations for oral diseases were found to correlate with systemic pathologies. All socioeconomic indices were associated with caries and/or periodontal diseases. This study is the first in Colombia that uses national data on diagnoses assigned to medical and dental consultations. PCA revealed a clustering pattern of pathologies suggesting that they are highly associated one to each other.ConclusionCorrelations between consultations for oral and systemic diseases stratified by life cycle and socioeconomic indices highlight the importance of conducting epidemiological and public health characterizations and their associations. Identifying these factors is imperative in the prevention and management of both diseases.